Misdiagnose of fine needle aspiration biopsy - Rahma Yulinda Damanhuri; Maria Goreti Widiastuti; Poerwati Soetji Rahajoe (MKGK (Majalah Kedokteran Gigi Klinik) (Clinical Dental Journal) UGM, 2017)
The accuracy of biopsy on oral malignant lesion examination depends on the adequacy of clinical information obtained, biopsy type and procedure, determination of biopsy site, and integrity of biopsy tissue. Fine needle aspiration biopsy (FNAB) is one of among cytology examinationthat can be used for oral lesion. However, the results are variative, either false positive or false negative. The adequate management of a malignant lesion started with an accurate diagnosis. Histopathology and tissue biopsy examination is a gold standard in diagnosis determination of suspected malignant lesion. The aim of this case study was to report a refferal case of misdiagnosed lower lip squamous cell carcinoma using FNAB examination. Patient reffered from local hospital with squamous cell carcinoma lesion misdiagnosed as a benign cystic lesion prone to mucocele through FNAB finding. From this case study, it was concluded that FNAB examination is not reliable to diagnose superficial lesions, such as cystic lesions and SCC in the lower lip. ABSTRAKKetepatan diagnosis dari pemeriksaan lesi ganas rongga mulut tergantung pada adekuatnya informasi klinis yang didapatkan, jenis dan prosedur biopsi yang tepat, pemilihan tempat biopsi dan pemenuhan syarat dari jaringan biopsi. Aspirasi jarum halus (AJH) merupakan salah satu pemeriksaan sitologi yang bisa dilakukan untuk lesi di mulut, namun hasil pemeriksaan AJH masih ada yang dilaporkan false negative maupun false positive dengan hasil yang bervariasi.Penanganan yang tepat pada lesi ganas dimulai dengan melakukan diagnosis yang akurat. Standar baku dalam mendiagnosa terletak pada pemeriksaan histopatologi dari biopsi jaringan yang dicurigai mengalami lesi ganas. Tujuan studi kasus ini adalah melaporkan suatu kasus rujukan kesalahan diagnosis squamous cell carcinoma bibir bawah dengan pemeriksaan AJH. Seorang pasien rujukan dari salah satu RSUD dengan lesi squamous cell carcinoma yangdidiagnosis benigna cystic lesion yang condong ke mucocele melalui pemeriksaan AJH. Kesimpulan studi kasus ini adalah pemeriksaan AJH tidak tepat digunakan untuk kasus lesi superfisial seperti lesi kistik dan SCC di bibir bawah.